The effect of fentanyl, DNQX and MK-801 on dorsal horn neurones responsive to colorectal distension in the anaesthetized rat. - Kozlowski, C; Bountra, C; Grundy, D (2000)
Certain dorsal horn neurones respond in a graded manner to noxious colorectal distension (CRD). Morphine inhibits these responses in the spinalized rat, but the role of excitatory amino acids in baseline visceral nociceptive transmission is less clear. This study examines the effect of the mu-opiate receptor agonist fentanyl, and the non-NMDA and NMDA antagonists DNQX and MK-801, respectively, on such responses to CRD in the sodium pentobarbitone-anaesthetized rat. Male rats were prepared for extracellular recording from the lumbosacral spinal cord. 90 neurones responsive to CRD, located throughout the dorsal horn, were classified according to their response duration and latency to 60 mmHg distension, as SL-A (short latency-abrupt; 59%), SL-S (short latency-sustained; 23%), L-L (long-latency; 10%) and Inhib (inhibited; 8%). Convergent cutaneous receptive fields were mapped for 79/90 neurones and classified as LT (low threshold), WDR (wide dynamic range) or HT (high threshold). CRD (20-100 mm Hg) elicited graded responses in most neurones. In 6/6 SL-S neurones, fentanyl (1-8 microg kg-1) dose-dependently inhibited the response to 60 mm Hg CRD, in a naloxone-sensitive manner, with an ID50 value (+/-95% confidence limits) of 2.48 (1.7-3. 7) microg kg-1. In 6/6 SL-A neurones, fentanyl had no significant effect on the response to CRD. DNQX (0.03-3 mg kg-1) produced a dose-dependent inhibition of the response to CRD in 5/5 SL-A neurones, with an ID50 value of 0.32 (0.01-41.1) mg kg-1. MK-801 (0. 03-0.3 mg kg-1) had no significant effect on responses to CRD in 6/6 SL-A neurones. The differential inhibitory effects of fentanyl on two neuronal subtypes may indicate functional differences. In SL-A neurones AMPA/kainate, but not NMDA receptors are involved in mediating baseline nociceptive neurotransmission.